Autologous Internal Limiting Membrane Fragment Transplantation for Rhegmatogenous Retinal Detachment Due to Paravascular or Juxtapapillary Retinal Breaks Over Patchy Chorioretinal Atrophy in Pathologic Myopia. Issue 1 (January 2018) - Rizzo, Stanislao; Tartaro, Ruggero; Barca, Francesco; Bacherini, Daniela; Franco, Fabrizio; Caporossi, Tomaso
Abstract : Supplemental Digital Content is Available in the Text.